Alternativas no ensino de línguas para surdos - Vilchez Jiménez, Elsa (1998)
The word deafness or deafness has been used to designate total or partial hearing loss or absence. Deafness is a hearing disorder that has multiple etiologies at the level of the auditory organs, or at psychological levels.